Diversity and properties of key spider silks and webs - Mortimer, Beth; Vollrath, Fritz (Food Agricultural Sciences and Technology, 2015)
Spider silks are natural materials whose diversity surpasses other known silks and man-made polymers. This review covers exciting aspects of the diversity of spider silks and focuses on orb web silks. We argue that to understand silks as biological materials, their functionality must always be considered. The evolution of major ampullate silk provides a good example, as do the properties and functions of the six other silks produced and used by araneid orbweavers. The adhesive snares of the orb webs provide an excellent example of the evolution of two very different forms of silk to capture and hold insect prey, both the wet-glue ecribellate spiders, like the araneids, and the dry-hackled silk of the much older cribellate spiders, like the uloborids. The review concludes by examining how silks may be actively tuned by the spider by adjusting spinning and post-processing conditions. Throughout we argue that this diversity makes spider silks excellent models for polymer research and applications.